2003
DOI: 10.1093/jac/dkg254
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics and hospital-acquired Clostridium difficile-associated diarrhoea: a systematic review

Abstract: A systematic review of studies that investigated the association of antibiotics with hospital-acquired Clostridium difficile-associated diarrhoea (CDAD) was undertaken to summarize the strength of the evidence for this relationship. The results from the studies identified were considered after critically reviewing the design and conduct of each study. Although the majority of studies found an association with various antibiotics, antibiotic classes or components of antibiotic administration, most were limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
0
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(170 citation statements)
references
References 74 publications
(154 reference statements)
6
154
0
10
Order By: Relevance
“…Antibiotic prophylaxis is designed to mitigate the risk of S. aureus infection, especially in surgical patients; however, this frequently fails due to drug resistance (5). Importantly, antibiotic therapy suppresses human microbiota and promotes Clostridium difficile infection, which is also associated with increased morbidity and mortality (6,7). Several trials for vaccines and immune therapeutics were designed to prevent MRSA infection in hospital settings; these efforts have thus far failed to meet their study end points (4).…”
mentioning
confidence: 99%
“…Antibiotic prophylaxis is designed to mitigate the risk of S. aureus infection, especially in surgical patients; however, this frequently fails due to drug resistance (5). Importantly, antibiotic therapy suppresses human microbiota and promotes Clostridium difficile infection, which is also associated with increased morbidity and mortality (6,7). Several trials for vaccines and immune therapeutics were designed to prevent MRSA infection in hospital settings; these efforts have thus far failed to meet their study end points (4).…”
mentioning
confidence: 99%
“…C. difficile is a Gram positive spore-forming anaerobic pathogen, which has been shown to be capable of producing toxins and is frequently a cause of diarrhea and colitis. [61][62][63] Notably, a follow-on study by the same group found a positive association between mode of delivery, the gut microbiota and atopy risk. 64 Another such study focused on the microbial composition of even younger infants (i.e., 3 days old) (n = 46).…”
Section: Effect Of Early Feeding Regimementioning
confidence: 97%
“…There is currently no accepted systematic method to determine or stratify the risk of development of RCDI, but there is an abundance of retrospective and surveillance literature citing several factors associated with the development of both an initial episode of CDI and RCDI. Factors shown to repeatedly correlate with RCDI were increasing age (≥ 65 years old), antibiotic therapy, and concomitant use of acid-suppressing medications (proton-pump inhibitors most frequently studied) (5)(6)(7)(12)(13)(14)(15)(16). While these factors were the most commonly cited, there are many other factors individually studied and found to be independently associated with CDI/RCDI including obesity, intraabdominal or gastrointestinal surgery, tube feedings or nasogastric tubes, inflammatory bowel disease (IBD), and immunocompromising disease states or medications (1,4,(17)(18)(19)(20)(21).…”
Section: Clostridium Difficile Infection (Cdi) Occurs Whenmentioning
confidence: 99%